1993
DOI: 10.1144/0040609
|View full text |Cite
|
Sign up to set email alerts
|

Heavy mineral stratigraphy in the UK Trias: Western Approaches, onshore England and the Central North Sea

Abstract: Population studies on the detrital heavy minerals (64-250 um, specific gravity >2.92) of the Trias in the North Sea Basin demonstrate that there are well-defined regional and stratigraphical variations which are of use in correlation and palaeogeographic reconstruction. Two provinces are recognized: a region comprising the Southern North Sea, onshore England and the English Channel; and a Central North Sea Area.The heavy mineral assemblages of the Triassic sandstones of the Southern North Sea, onshore England … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
10
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
4
10
1
Order By: Relevance
“…Svendsen & Hartley (2002) recognised apatite, garnet, monazite, titanite, tourmaline Otter Sandstone Fm. range (this study)* 2.5-13.5 11.0-64.0 <0.5-27.5 <0.5-5.5 0.5-7.0 0.0-0.5 9.5-31.0 5.0-32.5 mean (this study)* 7.1 44.2 7.9 1.9 4.0 0.1 17.8 16.9 range (Jeans et al, 1993) n.i. 26-50 3-14 n.i.…”
Section: Heavy-mineral Assemblagesmentioning
confidence: 50%
See 4 more Smart Citations
“…Svendsen & Hartley (2002) recognised apatite, garnet, monazite, titanite, tourmaline Otter Sandstone Fm. range (this study)* 2.5-13.5 11.0-64.0 <0.5-27.5 <0.5-5.5 0.5-7.0 0.0-0.5 9.5-31.0 5.0-32.5 mean (this study)* 7.1 44.2 7.9 1.9 4.0 0.1 17.8 16.9 range (Jeans et al, 1993) n.i. 26-50 3-14 n.i.…”
Section: Heavy-mineral Assemblagesmentioning
confidence: 50%
“…The range of minerals present is closely comparable to that recorded by Thomas (1902Thomas ( , 1909, who also recognised other minerals in very minor amounts (actinolite, kyanite, sillimanite, serpentine, topaz), but failed to identify apatite, owing to the use of hydrochloric acid during sample preparation. Jeans et al (1993) identified common apatite, garnet, rutile, tourmaline, staurolite and zircon, together with minor titanite. Svendsen & Hartley (2002) recognised apatite, garnet, monazite, titanite, tourmaline Otter Sandstone Fm.…”
Section: Heavy-mineral Assemblagesmentioning
confidence: 99%
See 3 more Smart Citations